Marketing Strategy Through Digital Marketing Efforts to Increase Occupancy in Homestay in Kuta Lombok - Firman Koma Febdilan; Muhammad Sultan Hali; Ayu Gardenia Lantang (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to find out what strategies are used by the homestay managers in an effort to increase occupancy for visits to homestays in Kuta Mandalika, Central Lombok. This research also aims to find out what The influence of online reservations on increasing visits to the Kuta Mandalika Lombok homestay Middle. This research uses a qualitative descriptive method. Data collection was carried out using interview, observation and documentation techniques. Meanwhile, data analysis is used by identifying, understanding, and organizing the data that has been obtained through observations, interviews, literature reviews, focus group discussions and documentation. Through p It can be stated that the homestay manager in Kuta Mandalika, Central Lombok using strategies in homestay marketing through digital marketing as well Online reservations have a significant influence in increasing occupancy visit the Mandalika Kuta homestay, Central Lombok. It can be concluded that the manager Many homestays use the Facebook platform to market homestays in Kuta Mandalika Lombok